Risk Assessment Kesehatan dan Keselamatan Kerja (K3) pada Pekerjaan Bongkar Menggunakan Metode Hazard Identification, Risk Assessment, & Risk Control pada Pelabuhan Ciwandan di Banten - Susiarni Magdalena; Harri Mochamad Mansur; Dwi Endah Kurniasari; Jaja Miharja (Universitas Muhammadiyah Yogyakarta, 2022)
Unloading work at the port has a high risk. Thus, Occupational Health and Safety (K3) through risk assessment must always be considered so that it meets K3 standards so that the risk of work accidents can be reduced. This study aims to conduct a K3 risk assessment on unloading work using the HIRARC (hazard identification risk assessment control) method at the Ciwandan Port in Banten. This exploration is an assessment that concentrates on using a subjective methodology with the stages of a basic review, problem planning, and examination objectives, sharing information, managing HIRARC data, investigating the report, and making conclusions. The consequence of this study shows that the risk rating that can be identified is at least 2 Low, 7 High, and 8 Emergency from the aspect of working environment conditions, activities, and mental conditions of Ciwanden Banten Port workers. So it can be concluded that there are aspects of K3 that have a high risk and require higher attention. Therefore, further research is needed regarding risk control that can be provided based on a risk assessment from the word related to the Health and Safety (K3) technique HIRARC (Hazard Identification, Risk Assessment, and Risk Control) at the Port of Ciwandan in Banten.